Identification of key genes and immune infiltration mechanisms in limb ischemia-reperfusion injury: a bioinformatics and experimental study - Shi, Qiyun; Tian, Taotao; Li, Yanfeng (Frontiers in Immunology, 2025)
Aim of the studyTo establish a cross-tissue bioinformatics model for identifying conserved key genes and immune infiltration mechanisms in ischemia-reperfusion injury (IRI) with experimental validation in limb IRI, including pharmacological targeting of the WNT5A/PLC pathway.Materials and methodsTranscriptomic data from CTGF-stimulated cardiac myocytes (GSE36073) were analyzed as a surrogate for limb IRI due to shared pathological mechanisms. Random forest, LASSO regression, algorithms identified feature genes, validated in a rat limb IRI model using RT-qPCR, and histology. Pharmacological inhibition (WNT5A inhibitor Box5, PLC inhibitor U-73122) was performed to assess pathway involvement. Immune cell infiltration patterns were analyzed via CIBERSORT.ResultsFrom 169 differentially expressed genes (116 upregulated, 53 downregulated), machine learning identified four key genes (WNT5A, PLCG, ITPR1, CAMK2A), significantly upregulated in experimental limb IRI (P<0.01). Pharmacological inhibition confirmed their functional roles: Box5 and U-73122 treatment reduced expression of WNT5A and PLC versus IRI controls (P<0.05), showing IRI-induced muscle fiber disruption, edema, and inflammation. Immune analysis revealed myeloid polarization shifts (increased M1, decreased M2 macrophages; P<0.05). WNT5A correlated negatively with memory immune cells, while PLCG, ITPR1, and CAMK2A correlated with lymphocyte subpopulations.ConclusionWe identified a conserved molecular signature across cardiac and skeletal muscle IRI, with WNT5A/PLC pathway components as mechanistically validated therapeutic targets. Our cross-tissue bioinformatic approach, reinforced by pharmacological and histological evidence, provides a novel framework for IRI analysis when direct patient data are unavailable. Combined targeting of macrophage polarization and cellular activation the WNT5A/PLC axis may offer synergistic therapeutic potential.